INOVASI PERTUNJUKAN WAYANG PERJUANGAN LAKON UNTUNG SURAPATI SEBAGAI PENGUATAN PENGAJARAN NILAI-NILAI BELA NEGARA - Sunardi sunardi; Kuwato Kuwato; Sudarsono Sudarsono (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
ABSTRACT This paper aims to describe the innovation of wayangperjuangan (wayang of struggle) show entitled UntungSurapatias the reinforcement for the teaching of state defense values. There are three problems stud-ied, namely: (1) what is the description of lakonUntungSurapati; (2) how the innovation of the wayangperjuangan show entitledUntungSurapati; and (3) why wayangperjuangan show entitledUntungSurapati teaches about the state defense for the people. The problems are examined by the theory of innovation to show the novelty aspect of the wayangperjuangan show. The results of the study indicate that firstly, lakonUntungSurapati provides an overview of the intricacies in the struggle in defending the nation; secondly, the innovation of wayangperjuangan show lakonUntungSurapati is known through the novelty in making puppets, the renewal of puppet plays, and the renewal of wayangperjuangan music; and thirdly, the wayangperjuangan show has a significant contribution as a reinforcement for the teaching of the state defense values for the community through the example of UntungSurapati struggle in defending the country.